An Analytical Study of NPAs in Public Sector Banks in India - Raval, Manish Bhaskarbhai (Journal of Commerce and Trade, 2012)
When the funds lent by the bank become doubtful or irrecoverable, it is termed as non-performing assets (NPAs). Banks are required to make provisions for such NPAs. RBI has issued guidelines for the provision for NPAs. According to RBI guidelines assets are classified as standard assets, sub-standard assets, doubtful assets and loss assets. The per cent provision of 0.40 per cent, 10 per cent, 100 per cent and 100 per cent respectively are required to be made by the banks. The presented article attempts to find out the position of Gross NPAs and Net NPAs in public sector banks in India. Applying the test of hypothesis using the F-test, it is found that Gross NPAs to Total Assets Ratio shows decreasing trend. The article attempts to find out the ratio Gross NPAs and Net NPAs to Total Assets and Advances. This ratio shows fluctuating trend in all the public sector banks.